Feasibility study of a double resonant 8-channel 1H/ 8-channel 23Na receive-only head coil at 3 Tesla - Malzacher, Matthias; Chacón-Caldera, Jorge; Paschke, Nadia; Schad, Lothar R. (Magnetic resonance imaging, 2019)
Sodium (23Na) magnetic resonance imaging (MRI), especially brain applications are increasingly interesting since sodium MRI can provide additional information about tissue viability and vitality. In order to include sodium MRI in the clinical routine, a single RF setup is preferable which provides high sodium sensitivity and full proton performance in terms of signal-to-noise ratio (SNR) and parallel imaging performance. The aim of this work was to evaluate the feasibility of a double resonant receive (Rx) coil array for proton and sodium head MRI. The coil was designed to provide high sodium SNR and full proton performance comparable to commercial coils which are optimized for sodium MRI or for proton MRI, respectively. A measurement setup was built which comprised an 8-channel Rx degenerate Birdcage for sodium imaging and an 8-channel Rx array for proton imaging. The performance of the coil was evaluated against commercial sodium and proton coils using phantom and in-vivo measurements of two healthy volunteers.
Gesehen am 09.05.2019